Pembuatan Club Mading di SD Negeri 13 Kelapa Kampit Desa Mentawak - Apipah, Nur; Anggara, Leo; Pitaloka, Lola (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2025)
Club mading is a reading medium as well as a medium for presenting students' works. Club Mading is used as a forum for channeling and developing literacy skills in reading and writing. Through wall coverings, students can grow their enthusiasm because they can imagine and be creative according to their wishes and then display them on the wall boards. This research aims to create a social media club at SD Negeri 13 Kelapa Kampit. So that students can develop students' reading literacy skills. This research uses qualitative methods by understanding and observing surrounding phenomena written down in words. As well as using observation techniques by making direct observations at the location of the research object. Stages of creating a wall magazine as an effort to increase the literacy and creativity of students at SD Negeri 13 Kelapa Kampit.